KARAKTERISTIK IBU YANG MEMPUNYAI BALITA DENGAN KEJADIAN DIARE DI PUSKESMAS 4 ULU PALEMBANG TAHUN 2011 - Dini Kesumah, Nurdjani Dini Kesumah, Nurdjani (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2012)
ABSTRACT According to WHO, causes diarrhea up to 2 million child deaths globally every year. There are several factors that cause diarrhea, including infectious factors, malabsorption factors, dietary and physiological factors. The purpose of this study was to determine the characteristics of mothers who have infants with diarrhea in four health centers Ulu Palembang in 2011. The design of this research is descriptive research using non-random methods in Accidental Sampling technique, where the variables studied are all variables that includes (diarrhea, education, knowledge, work and use of clean water). The sample in this study were 30 mothers who have young children who come for treatment to the IMCI clinic 4 Ulu Health Center in 2011. This analysis is used to obtain a frequency distribution with the percentage of all the variables included characteristics of the mothers who have infants with diarrhea. The results of this study indicate that respondents with diarrhea were 26 respondents (86.7%) and diarrhea 4 respondents (13.3%), respondents based on higher education sebanyak19 respondents (63.3%) and low education as much as 11 respondents (36, 7%), high-knowledge respondents based on as many as 25 respondents (83.3%) and low knowledge of five respondents (16.7%), respondents by occupation who worked as many as 20 respondents (66.7%) and not berkeja 10 respondents (33.3%), respondents based on the use of clean water as much as 16 respondents (53.3%) and who do not clean as much as 14 respondents (46.7%). From the results of this study are expected to further improve health education, especially regarding the incidence of diarrhea in infants to mothers who have young children understand more about the incidence of diarrhea. ABSTRAK Menurut WHO, diare menyebabkan kematian hingga 2 juta anak dunia setiap tahun. Ada beberapa faktor penyebab diare yaitu faktor infeksi, faktor malabsorbsi, faktor makanan dan faktor fisiologis. Tujuan penelitian ini adalah untuk mengetahuan karakteristik ibu yang mempunyai balita dengan kejadian diare di Puskesmas 4 Ulu Palembang Tahun 2011. Desain penelitian ini adalah penelitian deskriftif dengan menggunakan metode non random dalam teknik Accidental Sampling, dimana variabel yang diteliti adalah semua variabel yang meliputi (diare, pendidikan, pengetahuan, pekerjaan dan penggunaan air bersih). Sampel pada penelitian ini adalah 30 ibu yang mempunyai balita yang datang untuk berobat ke MTBS puskesmas 4 Ulu Puskesmas Tahun 2011. Analisis ini digunakan untuk memperoleh gambaran distribusi frekuensi dengan presentase semua variabel yang meliputi karakteristik ibu yang mempunyai balita dengan kejadian diare. Hasil penelitian ini menunjukkan bahwa responden dengan diare sebanyak 26 responden (86,7%) dan tidak diare 4 responden (13,3%), responden berdasarkan pendidikan tinggi sebanyak19 responden (63,3%) dan pendidikan rendah sebanyak 11 responden (36,7%), responden berdasarkan pengetahuan tinggi sebanyak 25 responden (83,3%) dan pengetahuan rendah sebanyak 5 responden (16,7%), responden berdasarkan pekerjaan yang bekerja sebanyak 20 responden (66,7%) dan tidak berkeja 10 responden (33,3%), responden berdasarkan penggunaan air bersih sebanyak 16 responden (53,3%) dan yang tidak bersih sebanyak 14 responden (46,7%). Dari hasil penelitian ini diharapkan agar lebih meningkatkan penyuluhan kesehatan khususnya tentang kejadian diare pada balita agar ibu yang mempunyai balita lebih memahami tentang kejadian diare.